Rancang Bangun Server VoIP IP PBX pada Jaringan Politeknik Negeri Malang Berbasis Singleboard Circuit - Arinta Fadlil Fajar Wicaksono (Politeknik Negeri Malang, 2017)
Building VoIP technology requires a server called Elastix. Singleboard circuit device can be an alternative to cover the shortcomings of a PC as a VoIP server, to support practicum activities. The specifications for the quad-core processor and 1GB LPDDR2 memory are expected to be able to provide access to the latest version of the operating system to be able to produce better communication quality as I PPBX. This study designed a VoIP IP PBX server communication system at the Polinema Telecommunication Laboratory using the Elastix Linux operating system, to determine the quality of VoIP communication services and the performance of a single board circuit as an IPPBX server. The results of the research are 64 kbps bandwidth capacity capable of serving a customer capacity of 181 subscribers through 8 number of channels. QoS measurement obtained a delay value of 4.87091 ms; jitter of 18,265ms; packet loss of 0.71%; throughput of 0.2747 Mbit / sec. The singleboard circuit server is capable of serving VoIP communications for as many as 20 users and 10 calls simultaneously on the same server with a cpu usage percentage of 17.7% and 17.2% cpu usage, when communicating with other servers.